2001
DOI: 10.1007/bf03167720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the anaesthetic agent isoflurane on the rate of neutrophil apoptosisin vitro

Abstract: Human neutrophil apoptosis is inhibited in a concentration-dependent manner in vitro by isoflurane in clinical concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Despite these findings that isoflurane may induce neurotoxicity, there have been many reports that isoflurane may protect against neurotoxicity (de Klaver et al, 2002; Gray et al, 2005; Kawaguchi et al, 2004; Li et al, 2008; Raphael et al, 2008; Tyther et al, 2001; Wise-Faberowski et al, 2004; Wise-Faberowski et al, 2001; Xu et al, 2008; Zaugg et al, 2000). Importantly, isoflurane's protection effects have been shown to be dose- and time-dependent.…”
Section: Effects Of Anesthetics On Aβ Levelsmentioning
confidence: 99%
“…Despite these findings that isoflurane may induce neurotoxicity, there have been many reports that isoflurane may protect against neurotoxicity (de Klaver et al, 2002; Gray et al, 2005; Kawaguchi et al, 2004; Li et al, 2008; Raphael et al, 2008; Tyther et al, 2001; Wise-Faberowski et al, 2004; Wise-Faberowski et al, 2001; Xu et al, 2008; Zaugg et al, 2000). Importantly, isoflurane's protection effects have been shown to be dose- and time-dependent.…”
Section: Effects Of Anesthetics On Aβ Levelsmentioning
confidence: 99%
“…In 1985 cases of cancer were described in nurses exposed to anaesthetics [74]. DNA single-strand breaks in peripheral lymphocytes of personnel with occupational exposure to anaesthetics has also been mentioned [75,76] as well as its effect on the rate of neutrophil apoptosis [77]. Chromosome analysis of samples from operating room personnel registered the same mutagenic changes [78].…”
Section: Air Monitoringmentioning
confidence: 99%
“…TYTHER et al (2001; found isoflurane and sevoflurane to cause dose-dependent inhibition of polymorphonuclear neutrophil apoptosis in vivo and in vitro. MOUDGIL and SINGAL (1997) showed that equipotent concentrations of isoflurane, enflurane, halothane and methoxyflurane in a gas mixture with 70% nitrous oxide influenced the chemotactic activity of neutrophils and monocytes.…”
mentioning
confidence: 93%
“…Isoflurane (TYTHER et al, 2001) and sevoflurane (TYTHER et al, 2003) were found to induce dose-dependent inhibition of polymorphonuclear neutrophil apoptosis in vivo and in vitro. as reported by MORISAKI et al (1998), total lymphocyte count did not change following sevoflurane anesthesia, but neutrophil count was observed to decrease while lymphocyte count increased.…”
mentioning
confidence: 97%